Sistem Informasi Pemesanan Ruang Rapat Terhadap Efisiensi Waktu Pada RSUD Pandan Arang Boyolali - Rimba Sudarmadi; Andik Prakasa Hadi; Edwin Zusrony (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
The development of information technology has had a significant impact on increasing efficiency in administrative management in many institutions, for example in hospitals. Pandan Arang Regional General Hospital (RSUD) Boyolali currently does not have a computerized system for the meeting room reservation process, which is still done manually, causing inefficiencies in services such as schedule conflicts, late confirmations, and errors in recording booking data. The purpose of this study is to design a web-based meeting room reservation information system to improve time efficiency in managing booking data. This study uses a descriptive quantitative approach with a development method using the Waterfall method starting from the needs analysis, design, implementation, and testing stages. The results of the study succeeded in creating an information system that can be used by employees to make meeting room reservations independently, quickly, and in real time, and makes it easier for ATR officers to manage booking data in a more structured manner. Based on black-box testing, the system is proven to run well and each feature has functioned according to user needs.